Portraits of Success: Building Personas from Scholarly Reading Patterns - Volentine, Rachel; Whitson, Liz; Tenopir, Carol (Qualitative and Quantitative Methods in Libraries, 2017)
Personas are frequently used in marketing and system designs to illustrate a specific demographic, attitude and/or behaviour, and their use can be translated into the academic and library setting.  The academic readership surveys conducted at universities in the United Kingdom in 2011 create a picture of the reading patterns of successful academic staff members.  These surveys build upon surveys conducted by Tenopir & King since 1977 at US and international universities.  Through the use of quantitative and qualitative techniques analyzing the participants’ most recent scholarly reading, such as where they obtain the material, the principal purpose of the reading, the value of the reading to the purpose, and how many articles and books they read, we can see not only how frequently they are accessing the library material but also the outcomes and values of the reading and how the library collections contribute to their work.  Successful faculty/academic staff members, for example those who published more journal articles and/or won awards in the past two years, read more scholarly material on average.  By analyzing the survey results, we can find behavioral patterns based on different demographic variables. Thereby, we can create personas illustrating reading patterns and qualities of successful academic staff, and can show how the library plays a crucial role in their success.